The Gaia-ESO Survey: asymmetric expansion of the Lagoon Nebula cluster NGC 6530 from GES and Gaia DR2. Issue 2 (27th March 2019) - Wright, Nicholas J; Jeffries, R D; Jackson, R J; Bayo, A; Bonito, R; Damiani, F; Kalari, V; Lanzafame, A C; Pancino, E; Parker, R J; Prisinzano, L; Randich, S; et al.
Abstract: The combination of precise radial velocities from multi-object spectroscopy and highly accurate proper motions from Gaia DR2 opens up the possibility for detailed 3D kinematic studies of young star-forming regions and clusters. Here, we perform such an analysis by combining Gaia -ESO Survey spectroscopy with Gaia astrometry for ∼900 members of the Lagoon Nebula cluster, NGC 6530. We measure the 3D velocity dispersion of the region to be5.35^+0.39_-0.34 km s −1, which is large enough to suggest the region is gravitationally unbound. The velocity ellipsoid is anisotropic, implying that the region is not sufficiently dynamically evolved to achieve isotropy, though the central part of NGC 6530 does exhibit velocity isotropy that suggests sufficient mixing has occurred in this denser part. We find strong evidence that the stellar population is expanding, though this is preferentially occurring in the declination direction and there is very little evidence for expansion in the right ascension direction. This argues against a simple radial expansion pattern, as predicted by models of residual gas expulsion. We discuss these findings in the context of cluster formation, evolution, and disruption theories.